POPULATION DYNAMICS OF RHIZOBACTERIA AND ITS POTENCY AS A BIOLOGICAL CONTROL AGENT TO CONTROL FUSARIUM DISEASE IN THE NURSERY OF AGARWOOD (Aquailaria malaccensis Lamrk) - Tri Wahyuni; Mulawarman Mulawarman; Nurhayati Damiri (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2015)
Agarwood is a resin product produced by particular trees and has a certain high comercial value. In Central Bangka Regency, agarwood is the main commodity of forest. The research was aimed to determine the dynamic population of rhizobacteria and its potential as a biological control agent to control Fusarium disease in the nursery of agarwood (Aquailaria malaccensis Lamrk). The research was carried out by using exploration and identification methods. Sixty nine bacterial isolates were obtained from 20 samples. The samples taken were from Pangkalan Baru and Koba districts. After selection process, 49 bacterial isolates were tested for the capacity of inhibition. Results showed that 37.50 % of the bacterial isolates indicated a strong inhibition capacity, meanwhile 58.33% indicated a moderate and only 4.70% possessed a weak inhibition. Pseudomonas fluorescens, P. aerogi-nosa, P. malthophilia and Klebsiella pnemoniae were identified from the selected isolates. These bacteria were potentially able to protect plants against Fusarium disease and to promote plant growth. This research needed to be continued at the field level in order to know the real effects on plant.